2021
DOI: 10.1017/s0950268821000200
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the detection, epidemiology and control ofCyclospora cayetanensiswith an emphasis on produce, water and soil

Abstract: Cyclospora cayetanensis is a parasite causing cyclosporiasis (an illness in humans). Produce (fruits, vegetables, herbs), water and soil contaminated with C. cayetanensis have been implicated in human infection. The objective was to conduct a scoping review of primary research in English on the detection, epidemiology and control of C. cayetanensis with an emphasis on produce, water and soil. MEDLINE® (Web of ScienceTM), Agricola (ProQuest), CABI Global Health, and Food Science and Technology Abstracts (EBSCOh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In epidemic areas such as the U.S., contact with soil was also a risk factor associated with an outbreak in Florida and the relationship remained significant after multivariate analysis [ 8 ]. However, there is a scarcity of publicly available detection-method studies and on prevalence studies on soil [ 9 ]. To our knowledge, there have only been three previous studies that analyzed and found C. cayetanensis contamination in soil [ 10 , 11 , 12 ], each using different sample sizes, DNA extraction and/or molecular detection methods.…”
Section: Introductionmentioning
confidence: 99%
“…In epidemic areas such as the U.S., contact with soil was also a risk factor associated with an outbreak in Florida and the relationship remained significant after multivariate analysis [ 8 ]. However, there is a scarcity of publicly available detection-method studies and on prevalence studies on soil [ 9 ]. To our knowledge, there have only been three previous studies that analyzed and found C. cayetanensis contamination in soil [ 10 , 11 , 12 ], each using different sample sizes, DNA extraction and/or molecular detection methods.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, large foodborne cyclosporiasis outbreaks have been described in industrialized countries as well [19,20]. Food safety management systems are important elements in the prevention of cyclosporiasis [21][22][23]. A considerable hygiene-relevance of C. cayetanensis has been impressively demonstrated by outbreaks in travelers [24], on cruise ships [25], and by the demonstration of C. cayetanensis in tap water on trains even in an industrialized country [26].…”
Section: Introductionmentioning
confidence: 99%
“…The literature search was originally conducted in February 2020 as part of a scoping review of C. cayetanensis and used the following search string: Cyclospora OR cyclosporiasis OR cayetanensis (Totton et al, 2021). An update of this search was conducted on 26 December 2020 in MEDLINE ® (Web of Science ™ ), Agricola (ProQuest) and CABI Global Health, with no publication type or language restrictions.…”
Section: Liter Ature S E Arch and Eli G Ib Ilit Y Criteriamentioning
confidence: 99%
“…As mussels and clams tend to be sessile (Ashbaugh et al, 2012), their potential to transport oocysts over large distances is likely limited. Additionally, shellfish have never been implicated in published reports as the cause of any human outbreak, nor has eating shellfish been found to be associated with non-outbreak-associated human C. cayetanensis infection (Totton et al, 2021). Shellfish are, therefore, unlikely to be significant in the epidemiology of cyclosporiasis.…”
Section: Natural Exposure Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation